Perspectives on Green Chemistry and the Application of Nvivo 12 Software: A Case Study of Pandemic Period in Chemistry Education - Sri Mulyanti; Julia Mardhiya; Mar'attus Solihah (Scientiae Educatia: Jurnal Pendidikan Sains, 2022)
This case study aims to identify chemistry education students’ perspectives on attitudes and implementation of the principles of green chemistry during the COVID-19 pandemic. The participant of this study was 64 chemistry education students who, from the beginning, have conducted online learning, including practicum. The instrument of this research was an online questionnaire to gain the required information. The data were analyzed using NVivo 12 software and presented in percentages based on 12 principles of green chemistry: (1) potential waste generation reduction, (2) efficient use of raw materials, (3) application of environmentally safe production methods, (4) environmentally friendly chemicals, (5) safer additives, (6) minimal use of heat, (7) natural ingredients, (8) reaction products with minimal by-products, (9) the use of effective catalysts, (10) easily biodegradable products for the environment, (11) time management of hazardous products, and (12) anticipation for physical contact with hazardous materials. Moreover, 85% of the students agree that the 12th principle must be well applied. The research findings serve a discourse for lecturers to convince the students to understand and implement the principles of green chemistry in practicum activities, especially during the pandemic.